"Sharp downward, blunt upward": district maternal death audits' challenges to formulate evidence-based recommendations in Indonesia - a qualitative study - Ratnasari D. Cahyanti; Widyawati Widyawati; Mohammad Hakimi (BMC, 2021)
Abstract Background Indonesia, the largest archipelago globally with a decentralized health system, faces a stagnant high maternal mortality ratio (MMR). The disparity factors among regions and inequities in access have deterred the local assessments in preventing similar maternal deaths. This study explored the challenges of district maternal death audit (MDA) committees to provide evidence-based recommendations for local adaptive practices in reducing maternal mortality. Methods A qualitative study was conducted with four focus-group discussions in Central Java, Indonesia, between July and October 2019. Purposive sampling was used to select 7-8 members of each district audit committee. Data were analyzed using the thematic analysis approach. Triangulation was done by member checking, peer debriefing, and reviewing audit documentation. Results The district audit committees had significant challenges to develop appropriate recommendations and action plans, involving: 1) non-informative audit tool provides unreliable data for review; 2) unstandardized clinical indicators and the practice of "sharp downward, blunt upward"; 3) unaccountable hospital support and lack of leadership commitment, and 4) blaming culture, minimal training, and insufficient MDA committee' skills. The district audit committees tended to associated maternal death in lower and higher-level health facilities (hospitals) with mismanagement and unavoidable cause, respectively. These unfavorable cultures discourage transparency and prevent continuing improvement, leading to failure in addressing maternal death's local avoidable factors. Conclusion A productive MDA is required to provide an evidence-based recommendation. A strong partnership between the key hospital decision-makers and district health officers is needed for quality evidence-based policymaking and adaptive practice to prevent maternal death.